Dynamics of Leaf-Litter Biomass, Nutrient Resorption Efficiency and Decomposition in a Moso Bamboo Forest After Strip Clearcutting - Zheng, Yaxiong; Guan, Fengying; Fan, Shaohui; Yan, Xinrong; Huang, Lanying (Frontiers in Plant Science, 2022)
Strip clearcutting can significantly reduce the harvesting costs of moso bamboo forests. Although bamboo is characterized by rapid accumulation of biomass, it is still a concern that this management method may reduce long-term productivity. Nutrient cycling has long been considered essential for forests to maintain high primary productivity. However, nutrient cycling of bamboo forests after strip cutting has not been previously reported. We conducted a strip clearcutting experiment and surveyed the litter dynamics for one year. We assessed changes in litter nutrients in response to the cutting and calculated the nutrient resorption efficiency and litter decomposition rate to evaluate the effect on nutrient use efficiency and nutrient return. Our results showed that strip cutting had no significant effect on litter production and nutrient return in the moso bamboo forest (p>0.05). However, annual litter biomass and nutrient return in reserved belts (RB) were significantly higher than those in the control (CK) (p<0.05). P and K resorption efficiencies in RB were significantly higher than in CK during certain periods of bamboo growth (p<0.05). We also observed that the annual decay constant of CK was significantly higher than that of plots that were strip clearcut (SC) (p<0.05). Our results suggest that strip cutting does not affect nutrient use efficiency or storage in the short term.